Imagine-making disciples in youth ministry … that will make disciples - Nel, Malan (HTS teologiese studies, 2015)
Discipling youth may be one of the ‘missing links’ in developing missional thinking and missional local churches. This is even more so where churches suffer from a very obvious estrangement among generations. This article draws on the most recent literature on developing missional churches. The departure point is the argument of a the New Testament scholar, who refers to the description of Matthew 28:16–20 as the manifesto of the church – a manifesto that lies on the same level of value as the Shema of Israel: ‘Listen, o Israel, the Lord our God is the only One.‘ This manifesto wants to tell us how new and differently we have to think on how people come into the body and how people will stay in the body. Picking up on three of my theological premises this article will work with a research question: What kind of church will make disciples in youth ministry? It will also work towards theological suggestions on how to make disciples in youth ministry in such a way that young disciples will make disciples.